Fluoride in Bottled Waters Consumed in Northeastern Brazil - Maria Eliza Dantas Bezerra Romão; Franklin Delano Soares Forte; Fábio Correia Sampaio; Jocianelle Maria Félix Fernandes Nunes (Association of Support to Oral Health Research (APESB), 2023)
Objective: To assess the fluoride concentration of bottled waters from municipalities in northeastern Brazil. Material and Methods: Bottled mineral waters were purchased in two periods at different commercial places of four large municipalities (João Pessoa, Campina Grande, Patos, and Cajazeiras) in the Paraíba state. The municipalities selected to present the following annual average temperature: João Pessoa 26.5 °C, Campina Grande 23.3 °C, Patos and Cajazeiras 27.5 °C. Fluoride concentration was determined using a combined ion-specific electrode. Readings (in mV) were conducted in triplicates for each standard solution and converted into fluoride concentration (mg F/L) using the Excel® software. Results: A total of 72 samples from six brands of bottled water were analyzed. The fluoride concentrations of all samples were low (0.11-0.21mg/L) but higher than those reported on the label and varied among different batches of the same brand. Conclusion: The fluoride levels in bottled water vary among brands, and these actual values are not stated in the labels.